Determinants of Dividend Payout Policy in Emerging Markets: Evidence from the ASEAN Region - Le, Thi Thai Ha; Nguyen, Xuan Hung; Tran, Manh Dung (Asian Economic and Financial Review, 2019)
This study examines the determinants of dividend payout policy by analyzing the behavior of 226 nonfinancial firms in three emerging markets in the ASEAN region from 2012 to 2016. The OLS regression model is employed to investigate the impacts of firms’ characteristics and countries’ factor on dividend payout decisions. The results show that the dividend payout is positively related with profitability. In contrast, growth opportunity has a negative effect on dividend payout. Other factors such as firm size, free cash flow, financial leverage and liquidity have little or no significant relationships with dividend payout decisions. A further contribution of this research is that it considers the impact of law on firms and their investor relationships. The results from this analysis reveal that firms in countries with higher investor protection tend to pay more dividends.